FAKTOR-FAKTOR YANG MEMPENGARUHI BERAT BADAN LAHIR BAYI DI PUSKESMAS WILAYAH KABUPATEN BANYUMAS - Happinasari, Ossie; Suryandari, Artathi Eka (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
High or low hemoglobin levels and lack of LILA during pregnancy has an effect on birth weight because it can lead to impaired fetal growth in the womb. Objective: to identify the influence of Hb and LILA at the mother to birth weight. Survey with a cross sectional approach. Population research is all three trimesters pregnant women. Samples were determined by simple random sampling technique, a large sample is 225. The analysis of this study is the univariate analysis using frequency distribution, bivariate analysis using linier test. Results: the average level of Haemoglobin at third semester pregnancy is 11 g%, the average value of the upper arm circumference for pregnant women is 24,91cm and the average birth weight of baby is 2981 grams. There is influence on the value upper arm circumference to birth weigh (p-value 0.030) and there is no influence Â the level of Haemoglobin to birth weight (p-value 0,667). Keywords: Hb, Upper Arm Circumference, Pregnancy, Birth Weight Infants.